A study of queuing time in waiting line of supermarket at cashier counter by using simulation - Nur Atirah, Abit (2015)
This study focuses on queuing time in waiting line in relationship to the customer satisfaction. This study was conducted to the operational activity on cashier counter at one on the supermarket in Kuantan. This study applied simulation approach by using Arena Software to develop and simulate actual process at cashier counter. This study took one year duration to be completed. It is the quantitative study in which the performance is measured by the utilization for the whole system at cashier counter. By using simulation model on cashier counter, this is significant improvement on queuing time in waiting line by 30% on the normal duration (Recording 1 min 90 sec).